Marriage Dispensation in Modern Muslim Societies: A Study of Family Law in Indonesia and Morocco - Rachmat Ali Hasan Rifaie, Devie; Akbarizan, Akbarizan (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
The Islamic law in Indonesia and Morocco is based on different schools of thought, with Indonesia predominantly following the Shafi'i school, while Morocco adheres to the Maliki school. The differences in the schools of thought adopted by these two countries have implications for the age limits for marriage as stipulated in their respective Family Law. However, the disparity is not significantly vast, with only about one or two years of difference. Morocco, in determining the minimum age for marriage, closely aligns with Indonesia by referencing the Shafi'i and Hanbali schools. Morocco also requires the permission of a guardian if both prospective spouses are under 18 years old. This is somewhat similar to the practice in Indonesia, where marriages involving individuals below the legal age require a marriage dispensation granted by the court, obtained upon the request of the parents/guardians of the underage individuals, supported by compelling reasons and sufficient evidence.